2021
DOI: 10.1002/fsn3.2673
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC‐QTOF/MS‐based comparative metabolomics in pectoralis major of fast‐ and slow‐growing chickens at market ages

Abstract: The molecular regulatory mechanism underlying meat quality between different chicken genotypes remains elusive. This study aimed to identify the differences in metabolites and pathways in pectoralis major (breast muscle) between a commercial fast‐growing chicken genotype (Cobb500) and a slow‐growing Chinese native chicken genotype (Beijing‐You chickens, BYC) at market ages respectively based on ultra‐high‐performance liquid chromatography‐quadrupole/time of flight mass spectrometry (UHPLC‐QTOF/MS). Eighteen me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Previous studies indicated that phospholipids have more important roles in the formation of aroma volatiles during meat cooking than triglycerides, probably due to a much higher proportion of unsaturated fatty acids in phospholipids (Mottram, 1998;Jayasena et al, 2013). Additionally, the glycerophospholipid metabolism pathway was associated with chicken meat flavor (Zhang et al, 2022). In our study, several candidate genes were involved in phospholipid related pathways, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies indicated that phospholipids have more important roles in the formation of aroma volatiles during meat cooking than triglycerides, probably due to a much higher proportion of unsaturated fatty acids in phospholipids (Mottram, 1998;Jayasena et al, 2013). Additionally, the glycerophospholipid metabolism pathway was associated with chicken meat flavor (Zhang et al, 2022). In our study, several candidate genes were involved in phospholipid related pathways, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…CRLS1 silencing also reduced cardiolipin levels (Maekawa et al, 2019). GPCPD1 appeared to catalyze sn-glycero-3-phosphocholine to sn-glycerol 3-phosphate, which are two metabolomic biomarkers involved in the discrimination of meat quality characteristics in chicken breeds (Zhang et al, 2022). GPAM was identified as a potential gene associated with nonanal.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies proved that the concentration of glutathione declined in atrophic muscles due to reactive oxygen species, although Tachibana et al claimed that glutathione was highly detected in the denervation-induced muscle atrophy model; however, they speculated that the result was attributed to the brief duration of denervation [ 47 , 48 , 49 ]. Zhang et al found that glycerophospholipid metabolism and glutathione metabolism were significantly changed in breast muscle between slow-growth and fast-growth chickens, which were considered important functions in meat flavor [ 50 ]. From all of the above, we fully hypothesize that the improved body weight of line S chickens depended on alteration of valine, leucine, and isoleucine biosynthesis and glycerophospholipid metabolism, but the accompanying oxidative injury acquired glutathione metabolism to release.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified multiple factors that contribute to these issues, including the influence of lipid oxidation on the development of flavor [4] , [5] , and the role of feed efficiency in determining the flavor precursors present in chicken meat [6] . The connection between the concentrations of volatile compounds, taste-related amino acids, fatty acids, and metabolites has been established in relation to the sensory attributes and flavor profiles of chicken meat [7] , [8] . Traditional cooking methods and storage conditions can intensify flavor issues in chicken meat, leading to an off-flavor such as a warmed-over flavor due to lipid oxidation [4] .…”
Section: Introductionmentioning
confidence: 99%